Simple flows of pseudoplastic fluids based on dehaven model - Walicka, Anna (Zielona Góra: Uniwersytet Zielonogórski)
In this paper three simple flows of visco-plastic fluids of DeHaven type or fluids similar to them are considered. These flows are: Poiseuille flow in a plane channel, Poiseuille flow through a circular pipe and rotating Couette flow between two coaxial cylinders. After presentation DeHaven model it was presented some models of fluids similar to this model. Next it was given the solutions of equations of motion for three flows mentioned above.
Keywords: DeHaven fluid; similar fluids; simple flows